beta-Funaltrexamine (beta-FNA) and neural tumor response in mice - Zagon, I S; McLaughlin, P J; Takemori, A E; Portoghese, P S (European journal of pharmacology, 1985)
The effects of beta-FNA, a highly selective and irreversible mu opioid receptor antagonist, in altering tumor response in A/Jax mice inoculated with S20Y cells were determined. Inoculation of neuroblastoma cells in control subjects resulted in 100% tumor incidence within 16 days, and mean and median survival times of 36 and 35 days, respectively, following tumor inoculation. Tumor incidence and survival times were comparable to controls for mice given chronic injections of 2 mg/kg and 10 mg/kg beta-FNA every 48 h beginning 2 days after tumor inoculation. Tumor growth was subnormal in the 10 mg/kg beta-FNA group. Both dosages of beta-FNA were found to block morphine-induced analgesia for 48 h. These results suggest that, in and by themselves, mu receptors selectively antagonized by beta-FNA do not play an important role in neuro-oncogenic events.